A kind of activated carbon with high adsorption of dioxin and preparation method thereof

By constructing organic metal frameworks and activated carbon doping, and loading 镧-tungsten/titanium/titanium dioxide catalysts, it solves the problem of unsatisfactory adsorption effects of active carbon when dealing with two evils. Effect.

CN118988271BActive Publication Date: 2025-01-28广东韩研活性炭科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411227383.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-28
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The existing activated carbon has poor adsorption effect when treating dioxin, and its adsorption and decomposition ability of dioxin is insufficient, making it difficult to meet stricter emission standards.

Method used

By constructing organic metal frameworks and activated carbon doping, alkaline-NH2 and cymbal bases are formed to enhance the π-π dispersal force of activated carbon, and loaded the modified 钒-tungsten/titanium dioxide catalysts to degrade the villain.

Benefits of technology

It significantly improves the adsorption rate and degradation effect of activated carbon on the two evils, which can effectively reduce the concentration of the two evils in smoke and meet stricter emission standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high dioxin adsorption activated carbon and a preparation method thereof, and belongs to the technical field of activated carbon preparation. The method comprises the following steps: washing, drying and carbonizing rice husk to obtain material A; mixing ammonium metavanadate, ammonium metatungstate and deionized water, heating and stirring, adding nano titanium dioxide and lanthanum nitrate, stirring, roasting, cooling and grinding to obtain a catalyst; mixing the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water and material A, transferring to a polytetrafluoroethylene lined autoclave for sealing, heat preservation at 120-130°C, impregnation and vacuum drying to obtain high dioxin adsorption activated carbon; by constructing an organic metal framework and doping with activated carbon, the adsorption rate of dioxin at the active sites inside the activated carbon is increased; and at the same time, a lanthanum-modified vanadium-tungsten / titanium dioxide catalyst is loaded to improve the adsorption and degradation effect of activated carbon on dioxin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon preparation, and in particular relates to highly dioxin-adsorbing activated carbon and a preparation method thereof. Background Art

[0002] As one of the key methods for harmless treatment of urban domestic waste in my country, incineration technology plays an indispensable role in the field of waste treatment. However, with the continuous improvement of environmental awareness, people's emission standards for dioxin pollutants in flue gas are becoming increasingly stringent. In order to meet these more stringent standards, many waste incineration plants have widely adopted activated carbon adsorption to control dioxin emissions. However, the adsorption capacity of activated carbon is limited, and its adsorption and decomposition capacity for dioxins is not strong enough, which leads to the fact that the existing activated carbon adsorption technology does not show ideal results in the process of treating dioxins. Summary of the invention

[0003] The object of the present invention is to provide a highly dioxin-adsorbing activated carbon and a preparation method thereof, so as to improve the adsorption effect of the activated carbon on dioxins.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0006] S1. Wash the rice husk, dry it at 80°C for 10-20h, and carbonize it in a tubular furnace under nitrogen atmosphere to obtain material A;

[0007] S2, taking titanium dioxide and calcining it in a muffle furnace to obtain nano titanium dioxide;

[0008] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, heating and stirring, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 15-20 hours, and then placing in a muffle furnace for roasting, cooling, and grinding to obtain a catalyst;

[0009] S4. Mix the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water and material A, perform ultrasonic dispersion for 20-30 minutes, transfer to a polytetrafluoroethylene-lined autoclave, seal it, keep it at 120-130° C. for 6-8 hours, filter it, wash the solid phase, immerse it in methanol for 20-30 hours, and vacuum dry it at 60° C. for 3-4 hours to obtain the highly dioxin-adsorbing activated carbon.

[0010] As a preferred technical solution of the present invention, in step S1, the carbonization refers to heating the temperature to 600-700°C at a heating rate of 3°C / min and keeping the temperature for 2-3h.

[0011] As a preferred technical solution of the present invention, in step S2, the calcination refers to calcination at 500-550° C. for 6-8 hours.

[0012] As a preferred technical solution of the present invention, in step S3, the heating and stirring refers to stirring at 80° C. for 8-10 minutes.

[0013] As a preferred technical solution of the present invention, in step S3, the calcination refers to calcination at 400-450° C. for 2-3 hours.

[0014] As a preferred technical solution of the present invention, in step S3, the mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.23-0.24: 0.15-0.16: 30-40: 1.2-1.5: 0.05-0.07.

[0015] As a preferred technical solution of the present invention, in step S4, the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 6-8 mg: 0.51-0.53 g: 0.51-0.53 g: 9-10 mL: 1-2 mL: 20-30 g.

[0016] The highly dioxin-adsorbing activated carbon is prepared by the above-mentioned preparation method.

[0017] Beneficial effects of the present invention:

[0018] The invention discloses a highly dioxin-adsorbing activated carbon and a preparation method thereof. By constructing an organic metal framework and doping with activated carbon, it helps to form alkaline -NH2 and carbonyl groups, which can enhance the π-π dispersion force of the activated carbon and improve the adsorption rate of dioxins at the active sites inside the activated carbon. At the same time, a lanthanum-modified vanadium-tungsten / titanium dioxide catalyst is loaded to degrade dioxins, thereby improving the adsorption and degradation effect of the activated carbon on dioxins. DETAILED DESCRIPTION

[0019] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0020] Example 1

[0021] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0022] S1. Wash the rice husk, dry it at 80°C for 10 h, place it in a tubular furnace, heat it to 600°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2 h to obtain material A;

[0023] S2, taking titanium dioxide and placing it in a muffle furnace at 500° C. and calcining it for 6 hours to obtain nano titanium dioxide;

[0024] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 8 min, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 15 h, and then placing in a muffle furnace and roasting at 400° C. for 2 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0025] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.23:0.15:30:1.2:0.05:

[0026] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 20 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 120°C for 6 hours, filter them, wash the solid phase, and then immerse them in methanol for 20 hours, and vacuum dry them at 100°C for 3 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 6 mg: 0.51 g: 0.51 g: 9 mL: 1 mL: 20 g.

[0027] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.483ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.113ngTEQ / Nm 3 .

[0028] Example 2

[0029] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0030] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0031] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0032] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 9 min, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 18 h, and then placing in a muffle furnace and roasting at 425° C. for 2.5 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0033] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.235:0.155:35:1.35:0.06:

[0034] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 25 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 125°C for 7 hours, filter them, wash the solid phase, and then immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 7 mg: 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 g.

[0035] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.487ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.109ngTEQ / Nm 3 .

[0036] Example 3

[0037] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0038] S1. Wash the rice husk, dry it at 80°C for 20h, place it in a tubular furnace, heat it to 700°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 3h to obtain material A;

[0039] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 550° C. for 8 h to obtain nano titanium dioxide;

[0040] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 10 min, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 20 h, and then placing in a muffle furnace and roasting at 450° C. for 3 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0041] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.24:0.16:40:1.5:0.07:

[0042] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 30 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 130°C for 8 hours, filter them, wash the solid phase, and then immerse them in methanol for 30 hours, and vacuum dry them at 100°C for 4 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 8 mg: 0.53 g: 0.53 g: 10 mL: 2 mL: 30 g.

[0043] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.479 ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.112ngTEQ / Nm 3 .

[0044] Comparative Example 1

[0045] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0046] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0047] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0048] S3, taking ammonium metatungstate and deionized water, mixing, stirring at 80°C for 9 minutes, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 18 hours, and then placing in a muffle furnace at 425°C for 2.5 hours, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0049] The mass ratio of ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.39:35:1.35:0.06:

[0050] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 25 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 125°C for 7 hours, filter them, wash the solid phase, and then immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 7 mg: 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 g.

[0051] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.487ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.179ngTEQ / Nm 3 .

[0052] Comparative Example 2

[0053] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0054] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0055] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0056] S3, taking ammonium metavanadate and deionized water, mixing, stirring at 80° C. for 9 min, adding the nano titanium dioxide and lanthanum nitrate, continuing stirring for 18 h, and then placing in a muffle furnace and roasting at 425° C. for 2.5 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0057] The mass ratio of ammonium metavanadate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.39:35:1.35:0.06:

[0058] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 25 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 125°C for 7 hours, filter them, wash the solid phase, and then immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 7 mg: 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 g.

[0059] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.486ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.184ngTEQ / Nm 3 .

[0060] Comparative Example 3

[0061] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0062] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0063] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0064] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 9 min, adding the nano titanium dioxide, continuing stirring for 18 h, and then placing in a muffle furnace and roasting at 425° C. for 2.5 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0065] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water and nano titanium dioxide is 0.235:0.155:35:1.35:

[0066] S4. Take the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, mix them, ultrasonically disperse them for 25 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 125°C for 7 hours, filter them, wash the solid phase, and then immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 7 mg: 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 g.

[0067] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.485ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.173ngTEQ / Nm 3 .

[0068] Comparative Example 4

[0069] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0070] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0071] S2. Mix 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A, perform ultrasonic dispersion for 25 minutes, transfer to a polytetrafluoroethylene-lined autoclave, seal it, keep it at 125°C for 7 hours, filter it, wash the solid phase, immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 g.

[0072] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.489ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.314ngTEQ / Nm 3 .

[0073] Comparative Example 5

[0074] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0075] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0076] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0077] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 9 min, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 18 h, and then placing in a muffle furnace and roasting at 425° C. for 2.5 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0078] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.235:0.155:35:1.35:0.06:

[0079] S4. Mix the catalyst, terephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water and material A, perform ultrasonic dispersion for 25 minutes, transfer to a polytetrafluoroethylene-lined autoclave, seal it, keep it at 125°C for 7 hours, filter it, wash the solid phase, immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, terephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water and material A is 7 mg: 0.52 g: 0.52 g: 9.5 mL: 1.5 mL: 25 mg.

[0080] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.488ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.241ngTEQ / Nm 3 .

[0081] Comparative Example 6

[0082] A method for preparing highly dioxin-adsorbing activated carbon comprises the following steps:

[0083] S1. Wash the rice husk, dry it at 80°C for 15h, place it in a tubular furnace, heat it to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere, and keep it warm for 2.5h to obtain material A;

[0084] S2, taking titanium dioxide and placing it in a muffle furnace and calcining it at 525° C. for 7 hours to obtain nano titanium dioxide;

[0085] S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, stirring at 80° C. for 9 min, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 18 h, and then placing in a muffle furnace and roasting at 425° C. for 2.5 h, cooling, grinding, and passing through an 80-mesh sieve to obtain a catalyst;

[0086] The mass ratio of ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide and lanthanum nitrate is 0.235:0.155:35:1.35:0.06:

[0087] S4. Mix the catalyst, deionized water and material A, disperse them ultrasonically for 25 minutes, transfer them to a polytetrafluoroethylene-lined autoclave, seal them, keep them warm at 125°C for 7 hours, filter them, wash the solid phase, immerse it in methanol for 25 hours, and vacuum dry it at 100°C for 3.5 hours to obtain the highly dioxin-adsorbing activated carbon; the dosage ratio of the catalyst, deionized water and material A is 7 mg:11 mL:25 mg.

[0088] The activated carbon was loaded into a fixed bed reactor and the reaction temperature was controlled at 110°C and the gas hourly space velocity was 2000 h -1 The dioxin concentration was 3.488ngTEQ / Nm 3 The flue gas dioxin concentration of garbage incineration was tested by activated carbon using the HJ / T365-2007 standard. The dioxin concentration of the flue gas after adsorption was 0.532ngTEQ / Nm 3 .

[0089] From the test results of the activated carbon prepared in Examples 1-3 and Comparative Examples 1-6 for adsorbing dioxins, it can be seen that the activated carbon prepared in Examples 1-3 of the present application has a good dioxin adsorption and degradation effect. This is because the present application constructs an organic metal framework and doping with activated carbon, which helps to form alkaline -NH2 and carbonyl groups, can enhance the π-π dispersion force of the prepared activated carbon, and improve the adsorption rate of dioxins at the active sites inside the activated carbon; at the same time, the lanthanum-modified vanadium-tungsten / titanium dioxide catalyst is loaded to degrade dioxins, thereby improving the adsorption and degradation effect of activated carbon on dioxins.

[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing highly dioxin-adsorbing activated carbon, characterized in that: The following steps are involved: S1. Wash the rice husk, dry it at 80°C for 10-20h, and place it in a tubular furnace in a nitrogen atmosphere for carbonization to obtain material A; S2, taking titanium dioxide and calcining it in a muffle furnace to obtain nano titanium dioxide; S3, taking ammonium metavanadate, ammonium metatungstate, and deionized water, mixing, heating and stirring, adding the nano titanium dioxide and lanthanum nitrate, continuing to stir for 15-20 hours, and then placing in a muffle furnace for roasting, cooling, and grinding to obtain a catalyst; S4. Mix the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water and material A, perform ultrasonic dispersion for 20-30 minutes, transfer to a polytetrafluoroethylene-lined autoclave, seal it, keep it at 120-130° C. for 6-8 hours, filter it, wash the solid phase, immerse it in methanol for 20-30 hours, and vacuum dry it at 60° C. for 3-4 hours to obtain the highly dioxin-adsorbing activated carbon.

2. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S1, the carbonization refers to heating the temperature to 600-700°C at a heating rate of 3°C / min and keeping the temperature for 2-3h.

3. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S2, the calcination refers to calcination at 500-550° C. for 6-8 hours.

4. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S3, the heating and stirring refers to stirring at 80° C. for 8-10 min.

5. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S3, the calcination refers to calcination at 400-450° C. for 2-3 hours.

6. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S3, the mass ratio of the ammonium metavanadate, ammonium metatungstate, deionized water, nano titanium dioxide, and lanthanum nitrate is 0.23-0.24: 0.15-0.16: 30-40: 1.2-1.5: 0.05-0.

07.

7. The method for preparing a highly dioxin-adsorbing activated carbon according to claim 1, characterized in that: In step S4, the dosage ratio of the catalyst, 2-aminoterephthalic acid, aluminum chloride hexahydrate, dimethylformamide, deionized water, and material A is 6-8 mg: 0.51-0.53 g: 0.51-0.53 g: 9-10 mL: 1-2 mL: 20-30 g.

8. An activated carbon with high dioxin adsorption prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation of water-soluble metal-organic framework composite material and application of water-soluble metal-organic framework composite material in detecting concentration of fluorine ions in water

    CN111454461A

  • Composite nano material for enriching and detecting dioxin and preparation method thereof

    CN111499880A